Bloomsbury Influences : Papers from the Bloomsbury Adaptations Conference, Bath Spa University, 5-6 May 2011.: Papers from the Bloomsbury Adaptations Conference, Bath Spa University, 5-6 May 2011. (2014) - Unknown
No abstract available